ANALISIS STRUKTUR OMAH SOKO PAPAT DI BLITAR TERHADAP RISIKO BEBAN GEMPA - Fajarwati, Anisah Nur; Yoganata, Yehezkiel Septian; Cahyani, Kharisma Nur; Rahman, Aulia; Kurniawan, Achendri M. (Prokons: Jurnal Teknik Sipil, 2024)
Omah Soko Papat is a traditional Javanese architectural structure characterized by four main wooden pillars (soko guru) that reflect its adaptability to environmental conditions, including earthquake risks. This study aims to analyze the structural strength of Omah Soko Papat under seismic and self-weight loads, focusing on the soko guru as a critical element. The analysis employed STAAD Pro v8i software and the response spectrum method to calculate internal forces and evaluate the capacity of teak wood as the primary material. The findings indicate that the combined compressive stress of 123.34 kg/cm² and shear stress of 0.83 kg/cm² remain below the allowable limits of 150.75 kg/cm² and 20.1 kg/cm², respectively. Furthermore, structural joints using 12.7 mm diameter bolts satisfy the required strength criteria, with a minimum of four bolts per joint. This study concludes that Omah Soko Papat demonstrates sufficient structural integrity as an earthquake-resistant construction while preserving aesthetic and cultural values. Integrating traditional design principles with modern technology provides a sustainable construction model adaptable to natural disasters. These results are expected to contribute to developing locally inspired, earthquake-resistant construction technologies suitable for seismic-prone regions.